Study of multi-objective optimization of process parameters in film posting based on outside mold decoration. (November 2018) - Zhigang, Li
In order to optimize the process parameters in film posting based on outside mold decoration (OMD), the polymethyl methacrylate (PMMA) plastic sheets were tested in uniaxial tensile tests at high temperature with different temperatures and strain rates. The coefficients of the viscoelastic constitutive model called Duan Saigal Greif Zimmerman (DSGZ) were calculated based on the uniaxial tensile tests, and the predicted curve of DSGZ model and experimental data were compared and analyzed. The user material subroutine in ABAQUS of the DSGZ model was designed and written by adopting elastic prediction-radial consumers algorithm and was integrated into ABAQUS for the simulation of forming process of mouse shell posting film using the OMD process. After solving the model, the film thickness distribution and its deforming distribution in the X - and Y -direction were obtained. The optimization objective was to minimize the standard deviation of film thickness and its deforming distribution in the X- and Y -direction for 50 nodes on the thin film of mouse shell. The process parameters of OMD were sampled based on the method of optimal Latin hypercube design. In addition, the radial basis functions model was built. As the analysis shows, the radial basis functions model is sufficiently accurate. Based on the models, the process parameters of OMD were multi-objective optimized and analyzed by adopting archive-based micro-genetic algorithm. The best process parameters group was obtained after comprehensive analysis.